2012
DOI: 10.1007/s00216-012-6003-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the HS-PTR-MS for online measurements of pyrethroids during indoor insecticide treatments

Abstract: A high-sensitivity proton transfer reaction mass spectrometer (HS-PTR-MS) has been used to study the temporal evolution of pesticide concentrations in indoor environments. Because of the high time variability of the indoor air concentrations during household pesticide applications, the use of this online high time resolution instrument is found relevant. Four pyrethroid pesticides of the latest generation that are commonly found in electric vaporizer refills, namely, transfluthrin, empenthrin, tetramethrin, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Tannenbaum employed chloride as a reagent ion to detect the chlorinated pesticide Aldrin (Tannenbaum et al, 1975). More recently, Vesin et al showed that high-sensitivity proton transfer reaction mass spectrometers can be calibrated to measure indoor concentrations in the 0.5-600 ppb v range of four pyrethroid pesticides with limits of detection (LODs) of 50 ppt v with 1 s time resolution (Vesin et al, 2012). However, these studies are limited by the use of a quadrupole mass spectrometer, which only has unit mass resolution (m/ m ∼ 1000) and thus limits the selectivity of the measurement.…”
Section: T Murschell Et Al: Gas-phase Pesticide Measurementmentioning
confidence: 99%
“…Tannenbaum employed chloride as a reagent ion to detect the chlorinated pesticide Aldrin (Tannenbaum et al, 1975). More recently, Vesin et al showed that high-sensitivity proton transfer reaction mass spectrometers can be calibrated to measure indoor concentrations in the 0.5-600 ppb v range of four pyrethroid pesticides with limits of detection (LODs) of 50 ppt v with 1 s time resolution (Vesin et al, 2012). However, these studies are limited by the use of a quadrupole mass spectrometer, which only has unit mass resolution (m/ m ∼ 1000) and thus limits the selectivity of the measurement.…”
Section: T Murschell Et Al: Gas-phase Pesticide Measurementmentioning
confidence: 99%
“…The household insecticide treatment exhibits high emission variability. Therefore, the measurements of the gaseous transfluthrin emitted by the electric vaporizer refills was performed with a High Sensitivity Proton-Transfer-Reaction Mass Spectrometer (HS-PTR-MS) (Ionicon Analytik), which provided on-line and high time-resolved measurements (Vesin et al, 2012). The HS-PTR-MS technique is based on chemical ionization of the molecules under study through H 3 O + transfer reactions, combined with subsequent mass spectrometric ion detection (Lindinger et al, 1998).…”
Section: Gas-phase Transfluthrin Measurementsmentioning
confidence: 99%
“…These include monitoring normal atmospheric VOC variations, anthropogenic VOCs, biogenic VOCs, and pollution monitoring. Different platforms have been utilized including field site measurements [67,68], vehicles [69], ships [70], and aircraft [71][72][73]. Some of these variations in the applications of PTR-MS are demonstrated in the snap shot of publications that follow: (i) measurements of VOCs of anthropogenic origin above a large city [69]; (ii) analysis of syngas in an industrial Fischer Tropsch process [74]; (iii) a comparison of PTR-MS with GC-MS of environmental analytes [75]; (iv) monitoring the atmosphere for pollutants near intensive farm animal production [76].…”
Section: Environmentalmentioning
confidence: 99%